Addressing Students’ Challenges in Acquiring Trigonometric Function Concepts: A Didactic Approach to Education for Sustainable Development - Senad Orhani (Journal of Education for Sustainable Development Studies, 2024)
The concepts of trigonometric functions constitute one of the main challenges that students face when studying mathematics in secondary and higher education. This paper addresses these challenges through a sustainable educational approach aligned with the principles of Education for Sustainable Development (ESD). The study identifies the main difficulties, such as graphical representation, real-life application of trigonometric functions and the conceptual understanding of angles and ratios. Through the methodology of observing students during lessons, weak points in the understanding of concepts such as the graphical representation of trigonometric functions, the use of trigonometric equations in real situations, and the difficulties arising from the lack of a clear connection between angles and ratios have been trigonometric identified. Based on these observations, didactic strategies have been proposed that include more interactive methods and the use of technology to improve student’s skills. The results of this study suggest that a new didactic approach, based on concrete examples and practical experience, helps to create a more stable and in-depth understanding of trigonometric functions. The findings of this study contribute to the development of educational practices focused on ESD, supporting students’ capacity to adapt, innovate, and engage in complex problem solving within mathematics education. Through a didactic approach that focuses on advanced teaching methods and the use of educational technology, this paper offers recommendations for improving teaching practices to facilitate the acquisition of complex mathematical concepts.